Highly conserved ribosome biogenesis pathways between human and yeast revealed by the MDN1-NLE1 interaction and NLE1 containing pre-60S subunits - Fiorentino, Federica; Thoms, Matthias; Wild, Klemens; Denk, Timo; Cheng, Jingdong; Zeman, Jakub; Sinning, Irmgard; Hurt, Ed; Beckmann, Roland (Nucleic acids research, 2025)
The assembly of ribosomal subunits, primarily occurring in the nucleolar and nuclear compartments, is a highly complex process crucial for cellular function. This study reveals the conservation of ribosome biogenesis between yeast and humans, illustrated by the structural similarities of ribosomal subunit intermediates. By using X-ray crystallography and cryo-EM, the interaction between the human AAA+ ATPase MDN1 and the 60S assembly factor NLE1 is compared with the yeast homologs Rea1 and Rsa4. The MDN1-MIDAS and NLE1-Ubl complex structure at 2.3 Å resolution mirrors the highly conserved interaction patterns observed in yeast. Moreover, human pre-60S intermediates bound to the dominant negative NLE1-E85A mutant revealed at 2.8 Å resolution an architecture that largely matched the equivalent yeast structures. Conformation of rRNA, assembly factors and their interaction networks are highly conserved. Additionally, novel human pre-60S intermediates with a non-rotated 5S RNP and processed ITS2/foot structure but incomplete intersubunit surface were identified to be similar to counterparts observed in yeast. These findings confirm that the MDN1-NLE1-driven transition phase of the 60S assembly is essentially identical, supporting the idea that ribosome biogenesis is a highly conserved process across eukaryotic cells, employing an evolutionary preservation of ribosomal assembly mechanisms.
Gesehen am 30.09.2025